Cortical Sensory Responses Are Enhanced by the Higher-Order Thalamus - Rebecca A. Mease (Cell Reports, 2016)
In the mammalian brain, thalamic signals reach the cortex via two major routes: primary and higher-order thalamocortical pathways. While primary thalamocortical nuclei transmit sensory signals from the periphery, the function of higher-order thalamocortical projections remains enigmatic, in particular their role in sensory processing in the cortex. Here, by optogenetically controlling the thalamocortical pathway from the higher-order posteromedial thalamic nucleus (POm) during whisker stimulation, we demonstrate the integration of the two thalamocortical streams by single pyramidal neurons in layer 5 (L5) of the mouse barrel cortex under anesthesia. We report that POm input mainly enhances sub- and suprathreshold activity via net depolarization. Sensory enhancement is accompanied by prolongation of cortical responses over long (800-ms) periods after whisker stimulation. Thus, POm amplifies and temporally sustains cortical sensory signals, possibly serving to accentuate highly relevant sensory information.